Features of applying decision-making methods to evaluation of financial stability of commercial banks - Ginevičius, Romualdas; Podviezko, Askoldas (Business: Theory and Practice, 2012)
The problem of evaluation of financial state of commercial banks has an extensive century-long history. The relevance of the topic increases upon  reappearing financial crises, such  as the contemporary crisis. The stable performance of financial intermediaries, mostly commercial banks in the bank-based system of Lithuania, ensures effective performance and growth of the economy in the country. The evaluation of stability of commercial banks is a tangled task, as their financial state depends on various conflicting criteria. Three major categories of evaluation methodologies are distinguished: rating agencies‘ methodolo-gies, and methodologies where econometric-statistical methods and decision-making aid (MCDA) methods are used. A survey of mentioned methodologies is provided, qualities of MCDA methods, which furnish prominence over other methods used in the evaluation of registered in Lithuania commercial banks are described. The proposed in the paper methodology is applied to the case of evaluation of eight major commercial banks registered in Lithuania.Article in Lithuanian.Sprendimų paramos metodų taikymo ypatumai vertinant finansinį komercinių bankų stabilumąSantrauka. Finansinės komercinių bankų būklės vertinimo problematika siekia šimtmečio istoriją, bet aktualumo nepraranda ir dabar, finansų krizės metu. Stabiliai funkcionuojantys finansiniai tarpininkai – komerciniai bankai užtikrina efektyvų ekonomikos funkcionavimą ir augimą. Finansinio komercinių bankų stabilumo vertinimas – sudėtingas uždavinys, nes finansinę komercinių bankų padėtį lemia įvairūs tarpusavyje konfliktuojantys kriterijai. Yra trys komercinių bankų vertinimo metodikų tipai: reitingavimo agentūrų metodikos, statistinius-ekonometrinius ir sprendimų paramos metodus taikančios metodikos. Straipsnyje, apžvelgiant jas visas, išryškinami daugiakriterinių sprendimų paramos metodų (MCDA) pranašumai kaip tinkamiausių metodų Lietuvos komercinių bankų finansiniam stabilumui vertinti. Pasiūlyta metodika pritaikyta Lietuvos komercinių bankų 2009 ir 2010 metų finansiniam stabilumui vertinti.Reikšminiai žodžiai: komerciniai bankai, bankų stabilumas, daugiakriteriniai metodai, PROMETHEE, CAMEL.